Resolvin D1 dampens pulmonary inflammation and promotes clearance of Nontypeable Haemophilus influenzae - Croasdell, Amanda (J Immunol, 2016)
Nontypeable Haemophilus influenzae (NTHi) is a gram-negative, opportunistic pathogen that frequently causes ear infections, bronchitis, pneumonia, and exacerbations in patients with underlying inflammatory diseases, such as chronic obstructive pulmonary disease. In mice, NTHi is rapidly cleared, but a strong inflammatory response persists, underscoring the concept that NTHi induces dysregulation of normal inflammatory responses and causes a failure to resolve. Lipid-derived specialized pro-resolving mediators (SPMs) play a critical role in the active resolution of inflammation by both suppressing pro-inflammatory actions and promoting resolution pathways. Importantly, SPMs lack the immune suppressive properties of classical anti-inflammatory therapies. Based on these characteristics, we hypothesized that aspirin-triggered resolvin D1 (AT-RvD1) would dampen NTHi-induced inflammation while still enhancing bacterial clearance. C57BL/6 mice were treated with AT-RvD1 and infected with live NTHi. AT-RvD1 treated mice had lower total cell counts and neutrophils in bronchoalveolar lavage fluid (BALF), and had earlier influx of macrophages. Additionally, AT-RvD1 treated mice showed changes in temporal regulation of inflammatory cytokines and enzymes, with decreased KC at 6hrs and decreased IL-6, TNFα, and Cox-2 expression at 24hrs post-infection. Despite reduced inflammation, AT-RvD1 treated mice had reduced NTHi bacterial load, mediated by enhanced clearance by macrophages and a skewing towards an M2 phenotype. Finally, AT-RvD1 protected NTHi-infected mice from weight loss, hypothermia, hypoxemia and respiratory compromise. This research highlights the beneficial role of SPMs in pulmonary bacterial infections, and provides the groundwork for further investigation into SPMs as alternatives to immunosuppressive therapies like steroids.